FORMULATION OF BROILER CHICKEN EGGSHELL NANOPARTICLE AS A SUNSCREEN - Amila
Indonesia is a tropical country in with high level sun radiation exposured, thus needed a sunscreen cosmetic in order to reduce amount of UV radiation penetrated through the skin and can minimized negative effect of exessive UV radiation, such as erytheme, aging and the possibility of skin cancer. This research aims is to use eggshell – a waste product as an active ingredients of sunscreen by reducing its particel size and to develop sunscreen preparation with a high Sun Protection Factor (SPF). The research begin with reducing the particle size of eggshell through wet milling proses using tumbler ballmill followed with sonication to produce a suspension of nanoparticle eggshell. Nanoparticles eggshell obtained were characterized based on its particle size, polidispersity index, and morphology using SEM. The sunscreen activity of the nanoparticle eggshell was previously determined using Q-Sun Xenon Test Chamber. The eggshell powder, either in the micro or nano size were formulated into cream dosage form using an oil in water base type concist of stearic acid, triethanoamine, lanolin, and cetostearyl alcohol. The creams formulated were evaluated pharmaceutically and its safety through irritation test on rabbit skin and eye, followed with in vivo determination of its sun protection effect in rabbit. Results showed that the nanoparticle size obtained through sonication method was 453.87±25.63 nm with polydispersity index of 0.16±0.04. The preliminary study of sun protection activity showed the cream containing 20% of nanoparticle size of eggshell applicated on the bluewool lengtherm 1.5-2 hours the time needed to fastness the bluewool color. The formula of the cream that meet with pharmaceutical requirement is formula consist of 5 and 8 % of eggshell nanoparticle in base containing 1% lanolin, 2% cetostearyl alcohol, 8% stearic acid and 1,6% triethanolamine. Through skin irritation test, the cream contained 8% of eggshell nanoparticle has mild category of irritation potency with IIP of 0.58. While on eye irritation test this cream has no effect. On in vivo assay, the cream contained 5 and 8 % of nanoparticle eggshell showed SPF value of 3.44 and 4.30, respectively, while the cream contained 8% of microparticel size of eggshell showed smaller SPF value i.e., 2.71. Based on this study, it can be concluded that reduction of particle size of eggshell into nanosize could increase the SPF value of sunscreen preparation.